Intravitreal Anti-Vascular Endothelial Growth Factor (VEGF) as an Adjuvant Before Vitrectomy for Proliferative Diabetic Retinopathy (PDR) - Winly; Fabiola Supit; Ni Made Ari Suryathi (Universitas Airlangga, 2023)
Introduction: The primary treatment in proliferative diabetic retinopathy (PDR) is vitrectomy; however, direct intervention to the dense proliferative fibrovascular membrane may lead to massive hemorrhage obscuring the surgery process. Purpose: to review the use of anti-vascular endothelial growth factor (VEGF) as an adjuvant therapy before pars plana vitrectomy in PDR cases. Review: Anti-VEGF has been proposed as an adjuvant preceding the vitrectomy to lower intraoperative and post-operative complications. On the other hand, it could increase fibrosis which triggers tractional retinal detachment (TRD) in PDR cases. Conclusion: Intervals of five to ten days are considered the most ideal between anti-VEGF injection and pars plana vitrectomy (PPV) surgery in which the adjuvant therapy has made neovascularization regression and before the occurrence of fibrovascular contractions.